Penetration Enhancing of an Erythrocyte-Mimicking Nanoplatform via Papaverine for Radiosensitization - Zhang J (Dove Medical Press, 2021)
Jinrui Zhang,1 Huaicheng Wang,1 Weilong Suo,2 Zhizhou Li,1 Chunxu Yang3 1Department of Orthopedics, China-Japan Union Hospital of Jilin University, Changchun, 130033, People’s Republic of China; 2Key Laboratory of Applied Chemistry and Nanotechnology at Universities of Jilin Province, Changchun University of Science and Technology, Changchun, 130022, People’s Republic of China; 3Department of Radiation and Medical Oncology, Hubei Key Laboratory of Tumor Biological Behaviors, Hubei Cancer Clinical Study Center, Zhongnan Hospital of Wuhan University, Wuhan, 430071, People’s Republic of ChinaCorrespondence: Zhizhou Li; Chunxu Yang Email zhizhou@jlu.edu.cn; youer9youer@163.comPurpose: Radiotherapy (RT) is recommended as an extensive therapeutic regimen for cancer patients; however, cancer radio-resistance results from reduced oxygen levels (hypoxia) in the tumor microenvironment. Herein, we report a therapeutic strategy that greatly enhances the treatment effects of RT.Methods: Specifically, papaverine (ppv), an FDA-approved smooth muscle relaxant, was applied in the strategy. Ppv improved blood flow via vasodilation to deliver sufficient oxygen to the hypoxic solid tumor and further resulted in increased tumor penetration of the radiosensitizer, significantly enhancing the radiosensitization compared with no ppv treatment. Additionally, tantalum oxide nanospheres were cloaked in red blood cell membranes (TaOx@M) to achieve greater biocompatibility, non-immunogenicity, and a longer circulation time.Results: As a high-Z element, tantalum provides localized dose enhancement and thereby boosts the efficacy of RT. Vasodilation, the oxygenation of cancer cells, and the improved accumulation and retention of TaOx@M in the tumor region were verified in vivo. Furthermore, compared with RT alone, the combined vasodilation and nanosphere camouflaging strategy more efficiently suppressed the growth of K7M2 tumors in mice.Conclusion: The results of this study suggest that the integration of TaOx@M and ppv has excellent potential for improving RT efficacy.Keywords: radiotherapy, hypoxia, tantalum oxide, papaverine, vessel vasodilation